A safe combined nephrectomy and right lobectomy using the liver hanging maneuver for huge renal cell carcinoma directly invading the right lobe of the liver: report of a case - Yoshimatsu, Masanori (Springer Japan, 2013)
We herein discuss a patient who underwent simultaneous combined right nephrectomy and right lobectomy of the liver. A 64-year-old male was diagnosed with a huge right renal cell carcinoma (RCC), 13 cm in diameter, which was invading directly into the right hepatic lobe. This type of RCC has been rarely reported, and an anterior approach using the liver hanging maneuver was extremely useful during hepatic parenchymal dissection. The liver parenchymal dissection was performed prior to mobilization of the liver, because the mobilization of the right lobe of the liver was impossible. During the hepatic parenchymal resection, the liver was suspended with the tape and transected, and thereafter, retroperitoneal dissection, nephrectomy and right lobectomy of the liver were completed. The patient was discharged from the hospital on the 12th postoperative day with an uneventful clinical course. The anterior approach using the liver hanging maneuver during hepatic parenchymal resection can be safe and feasible for huge RCC invading the right hepatic lobe.